A modern threat response framework. (April 2015) - Clay, Peter
Abstract : Time is of the essence when under cyber-attack, but for many organisations, the capability to rapidly respond to threats is hamstrung by a variety of factors that include a lack of skilled security professionals, outmoded manual change processes and patchwork infrastructures comprised of specialist point solutions. All of these factors conspire to slow response times when an organisation needs to be at its most decisive. Time is of the essence when under cyber-attack, but for many organisations, the capability to respond rapidly to threats is hamstrung by a variety of factors. These conspire to slow response times when an organisation needs to be at its most decisive. The solution of using automation to accelerate the response to threats requires a liberal dose of 'new' thinking – one that couples the speed of automation with streamlined change processes and leverages machine speed with human in the loop decision-making, explains Peter Clay of CSG Invotas.